2014
DOI: 10.1002/ebm2.6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of gene therapy in animal models of cerebral glioma: why did promise not translate to human therapy?

Abstract: BackgroundThe development of therapeutics is often characterized by promising animal research that fails to translate into clinical efficacy; this holds for the development of gene therapy in glioma. We tested the hypothesis that this is because of limitations in the internal and external validity of studies reporting the use of gene therapy in experimental glioma.MethodWe systematically identified studies testing gene therapy in rodent glioma models by searching three online databases. The number of animals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…However, findings from different laboratories, often from small studies, are inconsistent. Systematic reviews and meta-analysis are techniques to provide an unbiased and transparent summary of existing research [ 13 , 14 ]. They can be helpful in the design of clinical trials [ 15 , 16 ] and in understanding discrepancies between the results of preclinical and clinical trials [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, findings from different laboratories, often from small studies, are inconsistent. Systematic reviews and meta-analysis are techniques to provide an unbiased and transparent summary of existing research [ 13 , 14 ]. They can be helpful in the design of clinical trials [ 15 , 16 ] and in understanding discrepancies between the results of preclinical and clinical trials [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human glioma is derived from the neural ectoderm and is the most common type of primary malignant tumor in human brains (1). Also in China, human gliomas are the most common type of intracranial tumor, accounting for 40-50% (2).…”
Section: Introductionmentioning
confidence: 99%
“…The Collaborative Approach to Meta-Analysis and Review of Animal Data in Experimental Studies (CAMARADES) group have shown—for a range of experimental neurological diseases including glioma, stroke and multiple sclerosis—that reporting of measures to reduce risk of bias (such as randomisation and blinding) is poor and that publication bias is frequently present. These factors lead to a significant overstatement of perceived treatment efficacy [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%